Assessment of elite faba bean lines for enhanced productivity and resilience in contrasting challenging environments using phenotypic and molecular markers - Oumaima Chetto; Loubna Belqadi; Zain El Abidine Fatemi; Jamal Charafi; Mohamed Kouighat; Assia Najmi; Mohamed El Fechtali; Karim Houmanat; Abdelghani Nabloussi (Journal of Agriculture and Food Research)
Faba bean (Vicia faba L.) cultivation holds significant potential for enhancing agricultural sustainability, offering benefits such as increased grain yields, product diversification, and nutritional value. Despite facing abandonment by some farmers in Morocco, notably due to shifting agricultural practices, the cultivation of faba bean has maintained its leading position among legumes in the country. This study aims to revitalize interest in faba bean cultivation by addressing two main objectives: exploring genetic diversity among advanced germplasms, using phenotypic and ISSR molecular markers, and identifying promising elite lines under challenging conditions. Twenty elite advanced breeding lines, alongside five registered varieties, were evaluated at the Experimental Station of Douyet, National Agricultural Research Institute of Morocco over two successive years, using a Randomized Complete Block Design (RCBD). Agronomic traits, physiological data, and molecular analysis using ISSR primers were approached. Results demonstrated significant genotype influence across all traits, with significant variations observed between years with the exception of plants’ health focusing on anthracnose and botrytis and number of seeds per pod. Principal Component Analysis (PCA) revealed divergent responses of elite lines to environmental conditions. Noteworthy correlations were found, emphasizing the importance of the number of flowers per inflorescence as a selection criterion. While phenotypic clustering indicated high similarity, clustering using molecular analysis unveiled high diversity, highlighting unique genetic characteristics in certain genotypes. Interestingly, three elite lines (1, 16, and 22) significantly outperformed the leading varieties, in both seasons, and are under consideration for release as new faba bean varieties. Future research should focus on exploring quality attributes and resistance to pathogens in these distant genotypes, as understanding their unique traits is essential for furthering faba bean breeding and cultivation.